![](https://www1.michaeldemichele.com/img/nextpage1.png)
Suggested: solve by cramer's rule 5x-7y+z=11 6x-8y-z=15 3x+2y-6z=7 - 86- 15x-7(6x-9)-2 10x-5(2-3x) - 2x+3y=7 6x+5y=11 - 6x+7/3x+2=4x+5/2x+3 - 2x+3y-7=0 6x+5y-11=0 - y=6x-11-2x-3y=-7 substitution - (2x+3)-(5x-7)/6x+11=-8/3 - dy/dx=6x-2y-7/2x+3y-6 - calculate lim x→3 (x2-6x+5)/x 3-8x+7 - 8x-7-3x=6x-2x-3 - f(x)=2x3+3x2-36x+7 - 4x+3 6x+7 - f(x)=2x^3-3x^2-36x+7 - 36x+7 Browse related:
privacy contact
Copyright 2017 bapse
bapse is powered by Google and Youtube technologies
Thank you, for using bapse.
This site was designed and coded by Michael DeMichele,
and is being used as a portfolio demonstration. View more.